Habitat Quality Determines Dispersal Decisions and Fitness in a Beetle – Fungus Mutualism - Nuotclà, Jon Andreja; Diehl, Janina Marie Christin; Taborsky, Michael (Frontiers in Ecology and Evolution, 2021)
Delayed dispersal of sexually mature offspring is a fundamental component of cooperative breeding. In ambrosia beetles, female offspring temporarily remain in their natal nest and refrain from reproduction, instead investing in alloparental care. Previous work has demonstrated a link between helping behaviour and the increased need for pathogen defence arising from their close association with fungal cultivars. In the ambrosia beetle Xyleborinus saxesenii, mature female offspring can effectively fight pathogen infections and manage the microbial composition within the nest by adjusting the frequency of different hygienic and nest maintenance behaviours. This suggests a potential to respond flexibly to the ecology of their nest, which calls for a better understanding of the connection between behaviour and the microbial community thriving within their nests. Here, we studied the significance of the mutualistic fungus garden composition for the beetles’ nest ecology and fitness by experimentally varying substrate quality. We found that the vertically transmitted ambrosia fungus garden is composed of at least two fungus mutualist species and a wide variety of other microbes varying in their relative abundance. This is strongly affected by the moisture content of the substrate, which in nature depends on the age and type of wood. We found that the mutualist fungi complement each other in terms of dryness-resistance, allowing the beetles to utilise a broad range of substrates over prolonged time during which the wood gradually desiccates. Under suboptimal humidity conditions, the interaction between host and multiple fungus species has important ramifications for the behaviour of philopatric helpers, including their alloparental investment, sibling cannibalism and the timing of dispersal. Rearing five generations of beetles consecutively in dry substrate resulted in transgenerational effects on philopatry and alloparental care, probably mediated through the dominance of a particular fungus species that was driven by the experimental habitat condition. Interestingly, the nests of these selection lines produced much more offspring after five generations than any first-generation nest, which may have reflected increased egg laying by non-dispersing daughters. Our study highlights the importance of considering the interactions between the microbial community and their insect hosts for understanding social evolution in cooperatively breeding beetles.